Pancreatic Intraductal Papillary Mucinous Neoplasms: A Narrative Review - Paramythiotis, Daniel; Karlafti, Eleni; Fotiadou, Georgia; Charalampidou, Maria; Karakatsanis, Anestis; Ioannidis, Aristeidis; Michalopoulos, Antonios (Acta medica Lituanica, 2023)
Introduction: Intraductal papillary mucinous neoplasms (IPMNs) are the most frequent cystic pancreatic neoplasm. They derive from the main pancreatic duct or branch ducts.Aim: This narrative review aims to present and compare the current guidelines on the management of IPMNs.Materials and methods: We reviewed the most important scientific literature on the management of IPMNs.Discussion: The clinical presentation of IPMNs is usually non-specific; common symptoms are abdominal pain, weight loss, and jaundice. There are no sex differences, and the incidence increases with age. It is considered a premalignant lesion associated with synchronous or metachronous carcinomas. Multifocal sites within the pancreas and the presence of solid components, like mural nodules, are predictive factors for developing malignancy. Magnetic resonance imaging (MRI) is the imaging technique of choice. However, computed tomography (CT) and endoscopic ultrasound (EUS) with fine-needle aspiration (FNA) can also contribute to the diagnosis. Resection is the optimal treatment for IPMNs that arise from the main duct, while several indications are suggested for the surgery on IPMNs of branch ducts.Conclusion: The decision on surgery is not always a simple task and should be based on high-risk features of the neoplasm. In any case, re-examination and follow-up are highly recommended.